2009
DOI: 10.1148/rg.291085052
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern-based Approach to Assessment of Delayed Enhancement in Nonischemic Cardiomyopathy at MR Imaging

Abstract: Although delayed contrast material-enhanced cardiac magnetic resonance (MR) imaging has traditionally been used to evaluate ischemic disease and myocardial viability, it is increasingly being used in the evaluation of nonischemic cardiomyopathies. Unlike myocardial infarction, which demonstrates subendocardial or transmural delayed contrast enhancement in a vascular distribution, nonischemic cardiomyopathies demonstrate enhancement that is not limited to a vascular territory. In combination with other cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
115
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(122 citation statements)
references
References 29 publications
2
115
1
4
Order By: Relevance
“…Contrary to that septal involvement was hardly seen in our study [1,16] , which might reflect different underling etiologies of DCM (e.g. alcohol, drug intoxication).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to that septal involvement was hardly seen in our study [1,16] , which might reflect different underling etiologies of DCM (e.g. alcohol, drug intoxication).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, a midmyocardial streaky or spotty LGE localized basal or lateral was linked to HCM in our study and no preferred septal involvement was seen, which was reported by others before [1,11,17,18] . Again, differentiation from peri-/myocarditis was most sensitive by signal intensity, which was considerably weaker in HCM.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations